Seasonal Trends in Nonstructural Carbohydrates in Cool‐ and Warm‐season Grasses. Issue 5 (1st September 2014) - Jensen, Kevin B.; Harrison, Phil; Chatterton, N. Jerry; Bushman, B. Shaun; Creech, J. Earl
ABSTRACT: While increases in nonstructural carbohydrate (NSC) content of forages are generally considered advantageous, there are times during the growing season when grasses with increased NSC levels may not be the desired forage, particularly for horses ( Equus caballus) . Hence, there is a need to better understand carbohydrate trends across the growing season. This study evaluated 15 grass species from May to August (growth phase‐1) and from September to November (growth phase‐2) in northern Utah during 2004 and 2005 for sugars, fructans, water‐soluble carbohydrates (WSC), starch, and total nonstructural carbohydrates (TNC). Sampling date and species had a significant effect on carbohydrate concentrations in cool‐season grasses, with a lesser effect on warm‐season grasses. Warm‐season grasses had uniformly lesser sugar, fructan, WSC, and TNC concentrations than cool‐season grasses; however, they had dry‐matter yields (DMY) greater than cool‐season grasses in August. If high TNC forage is desired, then, of the grasses examined, perennial ryegrass and timothy would be the species of choice for irrigated pastures. However, if forage lower in TNC is desired, then meadow bromegrass, which had the least overall sugar, fructan, WSC, starch, and TNC concentrations, would be best. On dryland pastures, Sandberg bluegrass ( Poa secunda J. Presl.) and tall wheatgrass ( Thinopyrum ponticum (Podp.) Z.‐W. Liu and R.‐C. Wang) had the least overall forage carbohydrates, while crested wheatgrass ( Agropyron cristatum (L.) Gaertn.) maintained its carbohydrate concentrations better on 3 August. Fructan concentrations contributed 54, 47, and 42% of the total WSC concentrations in perennial ryegrass, crested wheatgrass, and Kentucky bluegrass, respectively, compared to 26 and 29% in tall wheatgrass and creeping meadow foxtail, respectively. Water‐soluble carbohydrates accounted for between 86 and 91% of the total TNC concentration in the cool‐season grasses compared to 75 to 80% in the warm‐season grasses.